Gambaran Kepuasan Mahasiswa Terhadap Mata Kuliah Pendidikan Budaya Anti Korupsi Di Jurusan Ortotik Prostetik Poltekkes Kemenkes Jakarta I Tahun 2017 - Payung Hasibuan (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
Background : Education service is intangible / service that can not be seen. One of the important factors for success or failure of students in attending lectures at educational institutions is the existence of good educational services and as expected for students. Objective : The purpose of this research is to know student satisfaction on lecturer performance in implementing Teaching and Learning Process of Anti Corruption Culture Education Course (PBAK) in Orthotics Prosthetics Poltekkes Kemenkes Jakarta I, 2017. Research Methodology : This was a descriptive exploration research. The sample in this study was determined by quota sampling with 38 respondents. Result of research : that result of student satisfaction to lecturer performance in Teaching and Learning Process implementation seen from five dimension of service quality as follows: tangibles dimension 97% satisfied, reliability 95% satisfied, responsiveness 74% satisfied, assurance 97% satisfied and empathy dimension (empathy) 97% satisfied. Conclusion : Almost all of students expressed satisfaction on the performance of lecturers in the implementation of Teaching and Learning Process Anti Corruption Culture Education (PBAK) Courses in the Prosthetic Orthotics Department, but in dimension 3, there is still less optimum responsiveness of students response (74% Satisfied) with the reason of dense college time. Recommendation : Need further research to see the causes of low dimension 3, regarding student responsiveness. Keywords: lecturer performance, student satisfaction, Anti Corruption Culture Education PBAK